ANALISIS TEORI MANAJEMEN KLASIK DALAM PENGEMBANGAN ORGANISASI PENDIDIKAN - Desi Amelia, Besse; Inmanora; Putri Dupa, Annuri; Muazza; Aprillitzavivayarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the relevance and application of classical management theory in the development of educational organizations in the modern era. A literature review was conducted by analyzing scholarly works, research reports, and educational policy documents from 2015 to 2025 that discuss the principles of Taylor, Fayol, and Weber, as well as their adaptation in school contexts. The analysis indicates that classical management theory still makes a significant contribution to building organizational structures that are efficient, disciplined, and accountable. However, rigid implementation can hinder innovation, creativity, and educator participation. Therefore, integrating classical principles with neoclassical approaches, transformational leadership, and educational technology becomes an effective strategy for creating adaptive, innovative, and learning-quality-oriented educational organizations. These findings confirm that classical management theory is not merely a historical concept but a foundational framework that can be modernized to address the challenges of 21st-century education.